Pengaruh Fasilitas Kerja dan Motivasi Kerja Terhadap Kepuasan Kerja di Pangeran Beach Hotel Padang - Mutri, Vanessa Bilbina; pasaribu, Pasaribu (Departemen Pariwisata Universitas Negeri Padang, 2025)
This research is motivated by issues related to work facilities and work motivation at Pangeran Beach Hotel Padang, which can influence job satisfaction. The objective of this study is to analyze the impact of work facilities and work motivation on job satisfaction at Pangeran Beach Hotel Padang. This study employs a quantitative method with an associative approach in the form of causal relationships, utilizing a survey method to examine the relationship between work facilities, work motivation, and job satisfaction. The data for this research was collected through the use of a research instrument in the form of a questionnaire distributed to 96 respondents. Hypothesis analysis in this study was conducted using multiple linear regression analysis with the assistance of SPSS version 16.00. The results indicate that there is an influence between work facilities and work motivation on job satisfaction, with an Adjusted R Square value of 0.666 or 66.6%, while 33.4% is influenced by other variables outside the scope of this study. Hypothesis testing in this research using multiple linear regression shows that the calculated F value is 95.643, with a table F value of 3.09, indicating that the calculated F value is greater than the table F value and is significant at 0.000 < 0.05. This demonstrates that the variables of work facilities (X1) and work motivation (X2) together have a significant effect on the variable of job satisfaction (Y).